A novel method of forceps biopsy improves the diagnosis of proximal biliary malignancies - Kulaksiz, Hasan; Strnad, Pavel; Römpp, Achim; von Figura, Guido; Barth, Thomas; Esposito, Irene; Schirmacher, Peter; Henne-Bruns, Doris; Adler, Guido; Stiehl, Adolf (Digestive diseases and sciences, 2011)
Background and Aims: Tissue specimen collection represents a cornerstone in diagnosis of proximal biliary tract malignancies offering great specificity, but only limited sensitivity. To improve the tumor detection rate, we developed a new method of forceps biopsy and compared it prospectively with endoscopic transpapillary brush cytology. Patients and Methods: 43 patients with proximal biliary stenoses, which were suspect for malignancy, undergoing endoscopic retrograde cholangiography were prospectively recruited and subjected to both biopsy [using a double-balloon enteroscopy (DBE) forceps under a guidance of a pusher and guiding catheter with guidewire] and transpapillary brush cytology. The cytological/histological findings were compared with the final clinical diagnosis. Results: 35 out of 43 patients had a malignant disease (33 cholangiocarcinomas, 1 hepatocellular carcinoma, 1 gallbladder carcinoma). The sensitivity of cytology and biopsy in these patients was 49 and 69%, respectively. The method with DBE forceps allowed a pinpoint biopsy of the biliary stenoses. Both methods had 100% specificity, and, when combined, 80% of malignant processes were detected. All patients with non-malignant conditions were correctly assigned by both methods. No clinically relevant complications were observed. Conclusions: The combination of forceps biopsy and transpapillary brush cytology is safe and offers superior detection rates compared to both methods alone, and therefore represents a promising approach in evaluation of proximal biliary tract processes.
Gesehen am 11.07.2022